Natural Phenylethanoid Supplementation Alleviates Metabolic Syndrome in Female Mice Induced by High-Fructose Diet - Zhan, Xiujun; He, Mingshuai; Pei, Jierong; Fan, Wenjing; Mwangi, Charity Ngina; Zhang, Peng; Chai, Xin; Jiang, Miaomiao (Frontiers in Pharmacology, 2022)
The aim of study is to evaluate whether salidroside (S), tyrosol (T) and hydroxytyrosol (H) which are dietary phenylethanoids of natural origins have an influence on reversing gut dysbiosis and attenuating nonalcoholic fatty liverfeatures of liver induced by metabolic syndrome (MetS) mice. C57 BL/6J female mice induced by high fructose diet were established and administrated with salidroside, tyrosol and hydroxytyrosol for 12 weeks, respectively. Biochemical analysis showed that S, T and H significantly improved glucose metabolism and lipid metabolism, including reduced levels of total cholesterol (TC), insulin (INS), uric acid (UA) and low-density lipoprotein cholesterol (LDL-C) and aspartate aminotransferase (ALT). Histopathological observation of liver confirmed the protective effects of S, T and H against hepatic steatosis, which was in accordance with the results of metabolomic analysis, including the improvement on glycolysis, purine metabolism, bile acid metaoblism, fatty acid metabolism and choline metabolism. Additionally, 16S rRNA gene sequence data further revealed that S, T and H could enhance the diversity of gut microbiota. In general, the abundance of Shigella, Acinetobacter, Lactobacillus, Staphylococcus and Sporosarcina had changed significantly. These findings suggest that S, T and H probably suppress lipid accumulation and to hepatoprotective effect and improve intestinal microflora disorders to attenuate metabolic syndromes.